2003
DOI: 10.1289/ehp.5917
|View full text |Cite
|
Sign up to set email alerts
|

Antiandrogenic activity and metabolism of the organophosphorus pesticide fenthion and related compounds.

Abstract: We investigated the endocrine-disrupting actions of the organophosphorus pesticide fenthion and related compounds and the influence of metabolic transformation on the activities of these compounds. Fenthion acted as an antagonist of the androgenic activity of dihydrotestosterone (10(-7)M) in the concentration range of 10(-6)-10(-4)M in an androgen-responsive element-luciferase reporter-responsive assay using NIH3T3 cells. The antiandrogenic activity of fenthion was similar in magnitude to that of flutamide. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 58 publications
(55 reference statements)
2
24
0
Order By: Relevance
“…In contrast, reverse reductive metabolism of methiocarb sulfoxide to methiocarb may be mediated by aldehyde oxidase. A similar observation has been made in the reduction of fenthion sulfoxide (Kitamura et al, 2003). The carbamoyl moiety in carbamate pesticides contains either an ester bond or an amide bond.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In contrast, reverse reductive metabolism of methiocarb sulfoxide to methiocarb may be mediated by aldehyde oxidase. A similar observation has been made in the reduction of fenthion sulfoxide (Kitamura et al, 2003). The carbamoyl moiety in carbamate pesticides contains either an ester bond or an amide bond.…”
Section: Discussionsupporting
confidence: 71%
“…In fact, we have reported that the anti-androgenic activity of fenthion, an organophosphate pesticide, is lost upon oxidation to fenthion sulfoxide by rat liver microsomes. However, the fenthion is recovered by the reduction of the sulfoxide (Kitamura et al, 2003). In contrast, the metabolites from the hydrolysis of methiocarb and carbaryl showed activities similar to or higher than those of the parent compounds.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Two major metabolites, MPP sulfoxide and MPP oxon were formed from MPP by some CYP and flavin-containig monooxygenase in the previously reported papers (Leoni et al, 2008;Kitamura et al, 2003). In their results, MPP sulfone and MPP oxon sulfone were not detected on chromatograms by HPLC/UV and GC/MS.…”
Section: Quantification Using Lc/ms Analysismentioning
confidence: 78%
“…It also lowered IMI-induced tGSH, while GPx decreased and CAT increased. Kitamura et al (68) reported that AOX catalysed fenthion metabolism to fenthion sulphoxide, and that this transformation was inhibited by MEN and β-oestradiol in the liver of male Sprague-Dawley rats. Similarly, Honda et al (8) reported that MEN decreased AOX activity in mouse fibroblast M10 cells.…”
Section: Effects Of Men On Imi Toxicitymentioning
confidence: 99%